2017
DOI: 10.1002/ece3.3460
|View full text |Cite
|
Sign up to set email alerts
|

Land use not litter quality is a stronger driver of decomposition in hyperdiverse tropical forest

Abstract: In hyperdiverse tropical forests, the key drivers of litter decomposition are poorly understood despite its crucial role in facilitating nutrient availability for plants and microbes. Selective logging is a pressing land use with potential for considerable impacts on plant–soil interactions, litter decomposition, and nutrient cycling. Here, in Borneo's tropical rainforests, we test the hypothesis that decomposition is driven by litter quality and that there is a significant “home‐field advantage,” that is posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 71 publications
3
14
0
Order By: Relevance
“…At both sites, almost 80% of the litter had decomposed after nine months in the forested habitats but <60% had decomposed in the converted habitats ( Figure 2) and soil respiration was consistently higher in the forest habitats (Figure 3). A similar decline in decomposition in degraded tropical forests was also found in an experiment in China, in which open deforested land had significantly lower decomposition rates than old-growth and regenerating forests (Paudel et al, 2015) and similar patterns were found in Sabah (Both et al, 2017). The lower rates of decay and soil respiration in the converted habitats can be explained by a combination of lower soil nutrient content (Table 1), greater variation in soil temperature and water content (Figure 3), and lower soil microbial biomass (Figures 4, 5) compared to the forest habitat.…”
Section: Habitat and Microclimate Influenced Decomposition Processessupporting
confidence: 81%
“…At both sites, almost 80% of the litter had decomposed after nine months in the forested habitats but <60% had decomposed in the converted habitats ( Figure 2) and soil respiration was consistently higher in the forest habitats (Figure 3). A similar decline in decomposition in degraded tropical forests was also found in an experiment in China, in which open deforested land had significantly lower decomposition rates than old-growth and regenerating forests (Paudel et al, 2015) and similar patterns were found in Sabah (Both et al, 2017). The lower rates of decay and soil respiration in the converted habitats can be explained by a combination of lower soil nutrient content (Table 1), greater variation in soil temperature and water content (Figure 3), and lower soil microbial biomass (Figures 4, 5) compared to the forest habitat.…”
Section: Habitat and Microclimate Influenced Decomposition Processessupporting
confidence: 81%
“…Yet while previous studies have for the most part been limited to making dichotomous comparisons between logged and unlogged forests, using high‐precision ALS data acquired across a landscape where land‐use intensity was manipulated experimentally we were able to characterize the effects of forest degradation on microclimate in terms of quantitative changes in forest structure. In doing so, our results underscore the importance of logged and secondary tropical forests not only for their biodiversity (Chazdon et al, ; Deere et al, ) and carbon storage potential (Martin, Newton, & Bullock, ; Poorter et al, ; Riutta et al, ), but also in terms of their ability to maintain environmental conditions conducive to forest regeneration and nutrient cycling (Both, Elias, Kritzler, Ostle, & Johnson, ; Ewers et al, ).…”
Section: Discussionsupporting
confidence: 57%
“…FD was more variable among logged forests than among old-growth forests (Fig. 4), probably owing to variation in logging history and intensity, which affect forest structure (Cannon et al, 1994;Berry et al, 2008), microclimatic conditions (Hardwick et al, 2015) and ecosystem functions (Mayfield et al, 2006;Both et al, 2017;Riutta et al, 2018). The substantial variance in FD among the disturbed plots highlights the challenge of predicting the impacts of anthropogenic modification on FD in environments where the outcomes may be highly context-dependent (Costantini et al, 2016).…”
Section: New Phytologistmentioning
confidence: 99%